Force-in-Chain Study of Chain-Electric Hoist with Periodical Variable Angular Rotational Velocity of Chain-Wheel (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Lifting mechanism of chain electric hoist with periodical variable angular velocity of chain-wheel has been studied in this paper. The non-uniform movement of chain is considerably decreased and from where the dynamic load is also decreased. The experimental studies of the lifting mechanism have been carried out at different operation modes. The results from these studies have been graphically presented and conclusions have been done.